Reliable exclusion of prognostically significant coronary disease in left ventricular dysfunction by cardiac MRI. Issue 2 (February 2017) - Thompson, A.C.M.; Crilley, J.G.; Wilson, D.W.; Hungin, A.P.S.; Fuat, A.; Murphy, J.J.M.
Abstract : Aim: To assess the ability of cardiac magnetic resonance (CMR) to exclude prognostically significant coronary artery disease (CAD) in patients with left ventricular systolic dysfunction (LVSD). Materials and methods: A cohort of patients who underwent both X-ray angiography and CMR since 2006 was reviewed retrospectively. Records of those with European criteria for LVSD (left ventricular ejection fraction [LVEF] <50% or LV end-diastolic volume index [LVEDVI] ≥97 ml/m 2 ) on CMR or transthoracic echo were analysed. The presence and extent of subendocardial late gadolinium enhancement (LGE) was recorded with the 17-segment model. The degree of coronary stenosis at X-ray angiography was assessed visually and significant disease defined as stenosis of the LMS ≥50%, or proximal left anterior descending ≥75%, or ≥70% in two main coronary vessels. Results: One hundred and sixteen patients were included. The mean age was 64 years and 78% were male. The mean LVEF was 40%. The prevalence of prognostic CAD was 47%. The presence of subendocardial LGE detected prognostically significant CAD with a sensitivity of 100% (95% CI: 94–100%) with no false-negative results. Conclusions: The absence of subendocardial LGE on CMR reliably excludes prognostic CAD in patients with LVSD. Highlights: CMR is a reliable screening tool for prognostic CAD in LV systolic dysfunction. Absent subendocardial LGE on CMR universally excluded prognostic CAD. Higher total LGE scores were more likely to predict prognostic CAD.